NARRATIVE DYNAMICS IN CROSS-CULTURAL POETRY: AN ANALYTICAL STUDY OF KANHAIYALAL SETHIA AND WILLIAM WORDSWORTH - Rao, Ashok Singh; Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Narratology, the study of narrative structures and techniques, is an effective tool for analyzing Kanhaiyalal Sethia and William Wordsworth’s poetry. Despite their origins in different cultural and historical contexts, both poets demonstrate mastery of narrative strategies that extend beyond their immediate surroundings. Sethia’s poetry, which is rooted in Rajasthani cultural and spiritual traditions, employs allegory, minimalism, and temporal fluidity to explore morality, spirituality, and human connection. Wordsworth, a key figure in English Romanticism, explores the interplay of nature, memory, and self-awareness through autobiographical reflection, vivid imagery, and temporal layering. This paper compares their narrative techniques, with a focus on narrative voice, temporal manipulation, symbolic imagery, and dialogic engagement. The study emphasizes the universality of their poetic themes as well as their distinctive contributions to literary narratology through textual analysis. This study highlights the poetry’s timeless relevance in shaping literary and cultural discourses by placing it within the larger framework of narrative theory.